2016
DOI: 10.1016/j.fertnstert.2016.08.028
|View full text |Cite
|
Sign up to set email alerts
|

Extremities of body mass index and their association with pregnancy outcomes in women undergoing in vitro fertilization in the United States

Abstract: Among women undergoing IVF, prepregnancy BMI affects pregnancy and obstetric outcomes. Underweight status may have a limited impact on pregnancy and live-birth rates, but it is associated with increased preterm and low-birth-weight delivery risk. Obesity negatively impacts all ART and obstetric outcomes investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
101
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(118 citation statements)
references
References 22 publications
14
101
3
Order By: Relevance
“…A large study that evaluated the influence of BMI on all autologous fresh in vitro fertilization (IVF) cycles in the United States from 2008 to 2013 ( n = 494 097 cycles, n = 402 742 transfers, n = 180 855 pregnancies) found that obese women had a statistically lower likelihood of intrauterine pregnancy (RR, 0.94; 95% CI, 0.94–0.95) and live birth (RR, 0.87; 95% CI, 0.86–0.88). Obesity has been associated with a significantly higher risk of miscarriages (RR, 1.23; 95% CI, 1.20–1.26) . These results are similar to those of other studies and meta‐analyses …”
Section: Discussionsupporting
confidence: 89%
“…A large study that evaluated the influence of BMI on all autologous fresh in vitro fertilization (IVF) cycles in the United States from 2008 to 2013 ( n = 494 097 cycles, n = 402 742 transfers, n = 180 855 pregnancies) found that obese women had a statistically lower likelihood of intrauterine pregnancy (RR, 0.94; 95% CI, 0.94–0.95) and live birth (RR, 0.87; 95% CI, 0.86–0.88). Obesity has been associated with a significantly higher risk of miscarriages (RR, 1.23; 95% CI, 1.20–1.26) . These results are similar to those of other studies and meta‐analyses …”
Section: Discussionsupporting
confidence: 89%
“…These, in turn, are shaped by more distal processes that affect maternal nutrition, maternal exposure to biological and psychosocial stress, maternal exposure to infection, and management of chronic conditions. Pregnancy survival varies with women's body mass index (Maconochie et al 2007;Arck et al 2008;Kawwass et al 2016), consumption of folic acid (Bailey and Berry 2005), and in some studies, reports of stressful life events (Arck et al 2008).…”
Section: Parental Exposures and Pregnancy Survivalmentioning
confidence: 99%
“…For obese nulliparous women the RR for very early preterm birth doubled (RR 1.99; 95% CI, 1.32–3.01). An analysis of all fresh autologous IVF cycles in the USA from 2008 to 2013 (494 097 cycles yielding 180 855 pregnancies) reported that among cycles resulting in singleton pregnancy, obesity was associated with increased risk of low birth weight (adjusted RR 1.26; 95% CI, 1.20–1.33) and preterm birth (adjusted RR 1.42; 95% CI, 1.36–1.48) …”
Section: Wellbeing Of the Childmentioning
confidence: 99%